Improved Methods for Fluorescence Microscopy Detection of Macromolecules at the Axon Initial Segment - Alshammari, Musaad A.; Alshammari, Tahani K.; Laezza, Fernanda (Frontiers in Cellular Neuroscience, 2016)
The axonal initial segment (AIS) is the subcellular compartment required for initiation of the action potential in neurons. Scaffolding and regulatory proteins at the AIS cluster with ion channels ensuring the integrity of electrical signaling. Interference with the configuration of this protein network can lead to profound effects on neuronal polarity, excitability, cell-to-cell connectivity and brain circuit plasticity. As such, the ability to visualize AIS components with precision provides an invaluable opportunity for parsing out key molecular determinants of neuronal function. Fluorescence-based immunolabeling is a sensitive method for morphological and molecular characterization of fine structures in neurons. Yet, even when combined with confocal microscopy, detection of AIS elements with immunofluorescence has been limited by the loss of antigenicity caused by fixative materials. This technical barrier has posed significant limitations in detecting AIS components alone or in combination with other markers. Here, we designed improved protocols targeted to confocal immunofluorescence detection of the AIS marker fibroblast growth factor 14 (FGF14) in combination with the cytoskeletal-associated protein Ankyrin-G, the scaffolding protein βIV-spectrin, voltage-gated Na+ (Nav) channels (especially the Nav1.6 isoform) and critical cell type-specific neuronal markers such as parvalbumin, calbindin, and NeuN in the mouse brain. Notably, we demonstrate that intracardiac perfusion of animals with a commercially available solution containing 1% formaldehyde and 0.5% methanol, followed by brief fixation with cold acetone is an optimal and sensitive protocol for FGF14 and other AIS marker detection that guarantees excellent tissue integrity. With variations in the procedure, we also significantly improved the detection of Nav1.6, a Nav isoform known for its fixative-sensitivity. Overall, this study provides an ensemble of immunohistochemical recipes that permit excellent staining of otherwise invisible molecules within well-preserved tissue architecture. While improving the specific investigation of AIS physiology and cell biology, our thorough study can also serve as a roadmap for optimizing immunodetection of other fixative-sensitive proteins expanding the repertoire of enabling methods for brain studies.